Jane Blonde, goldenspy - Marshall, Jill (Macmillan Children's Books, 2008)
When her spysuit is upgraded from silver to GOLD, Jane Blonde becomes the most dazzling spylet in the universe. But from his secret space station, her arch-enemy is launching a terrible weapon that threatens the zap the Goldenspy's spectacular powers